2008
DOI: 10.1163/156854008783797507
|View full text |Cite
|
Sign up to set email alerts
|

Two species of Crustacea (Decapoda) associated with the fan mussel, pinna nobilis Linnaeus, 1758 (Mollusca, Bivalvia)

Abstract: During a study on the ecology and biology of the fan mussel, Pinna nobilis along the northern and eastern coasts of Tunisia, the presence of the shrimp, Pontonia pinnophylax and the crab, Nepinnotheres pinnotheres (Decapoda) associated with this bivalve, was recorded. The shrimp was collected only in the lagoon of Bizerte, whereas the crab was found exclusively at Stah Jaber (close to the fishing port of Monastir). P. nobilis was occupied by Pontonia pinnophylax in 23.3% of the samples and the associated shrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The isotopic enrichment of the fan mussel guests in the present work was consistent with the estimated trophic level of the consumers (le loc 'h et al, 2008). The capacity for food selection may explain the differences in the contribution of the different food sources to their diets, since the morphology of both studied guests allows them to select food sources (Rabaoui et al, 2008). a previous study also demonstrated that the capacity for food selection generated variations in isotopic composition (decottignies et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The isotopic enrichment of the fan mussel guests in the present work was consistent with the estimated trophic level of the consumers (le loc 'h et al, 2008). The capacity for food selection may explain the differences in the contribution of the different food sources to their diets, since the morphology of both studied guests allows them to select food sources (Rabaoui et al, 2008). a previous study also demonstrated that the capacity for food selection generated variations in isotopic composition (decottignies et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
“…differences in the percentage contribution between δ 13 C and δ 15 n signatures by food sources such as PoM and soM have been reported previously (sarà et al, 2004). The contributions to δ 15 n signatures of invaded versus non-invaded P. pinnophylax showed little variation, almost avoiding the effect of the red macroalga L. lallemandii (4.1% of real contribution), perhaps due to its capacity for food selection (Rabaoui et al, 2008). in invaded versus non-invaded P. nobilis, the food sources showed variations in their percentage contribution to the δ 15 n signatures, with L. lallemandii making a real contribution of 19.4% in P. nobilis located in the invaded seagrass meadows.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is thought that N. pinnotheres live in P. nobilis as an impermanent refuge. Therefore, more than one male is encountered in the same P. nobilis (Rabaoui et al, 2008). At present, the population of P. nobilis is under significant threat on the Mediterranean coasts.…”
Section: Introductionmentioning
confidence: 99%